2019
DOI: 10.3389/fphar.2019.00805
|View full text |Cite
|
Sign up to set email alerts
|

Rhizoma coptidis as a Potential Treatment Agent for Type 2 Diabetes Mellitus and the Underlying Mechanisms: A Review

Abstract: Diabetes mellitus, especially type 2 diabetes mellitus (T2DM), has become a significant public health burden. Rhizoma coptidis (RC), known as Huang Lian , is widely used for treating diabetes in China. The bioactive compounds of RC, especially alkaloids, have the potential to suppress T2DM-induced lesions, including diabetic vascular dysfunction, diabetic heart disease, diabetic hyperlipidemia, diabetic nephropathy, diabetic encephalopathy, diabetic osteopathy, dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 220 publications
(222 reference statements)
0
20
0
2
Order By: Relevance
“…Scutellaria Radix (SR) and Coptidis Rhizome (CR) are well-known herbs applied for diabetes treatment since thousands of years and have demonstrated hypoglycemic effects in both clinical trials and basic experiments (Zhang et al, 2018 ; Ran et al, 2019 ). The combination of SR and CR (SC) exerted anti-diabetic activities through the TLR4 signaling pathway involved in anti-inflammation and gut microbiota regulation.…”
Section: Host-gut Microbiota-herbal Medicine Interaction During T2dm mentioning
confidence: 99%
“…Scutellaria Radix (SR) and Coptidis Rhizome (CR) are well-known herbs applied for diabetes treatment since thousands of years and have demonstrated hypoglycemic effects in both clinical trials and basic experiments (Zhang et al, 2018 ; Ran et al, 2019 ). The combination of SR and CR (SC) exerted anti-diabetic activities through the TLR4 signaling pathway involved in anti-inflammation and gut microbiota regulation.…”
Section: Host-gut Microbiota-herbal Medicine Interaction During T2dm mentioning
confidence: 99%
“…The root, stem, leaves and bark of these spiny shrubs (~500 species) are widely considered to be the main natural source of BBR. BBR has been traditionally used to treat diabetes as an active constituent of the Chinese herbs huόng liόn (Coptis Root) and huang băi (Phellodendron Chinese) (Chang et al, 2015a;Ran et al, 2019). Numerous clinical trials have demonstrated that BBR (0.6-2.7 g/day for 2-3 months) is effective for treating hyperglycemia, and hyperlipidemia in patients with type 2 diabetes mellitus (Zhang et al, 2008;Lan et al, 2015).…”
Section: Berberine (Bbr) Is An Isoquinoline Alkaloid Enriched In Planmentioning
confidence: 99%
“…ere is increasing evidence of a correlation between cell dysfunction/death and the onset of diabetes [11][12][13]. In the prediabetes stage of T2DM, pancreatic β-cell function is already diminished [14]. As the course of the disease progresses, the long-term high-glucose environment further damages the β-cells, leading to a gradual decline in insulin secretion and cellular apoptosis [15].…”
Section: Introductionmentioning
confidence: 99%